Building Resilient Healthcare Systems: A Comprehensive Review Of Medical, Nursing, Diagnostic, And Allied Health Contributions (The Review of Diabetic Studies, 2025)
Healthcare systems worldwide are increasingly exposed to complex and overlapping challenges, including pandemics, natural disasters, workforce shortages, and rising care demands. These pressures have highlighted the critical importance of healthcare system resilience—the ability to anticipate, absorb, adapt to, and recover from disruptions while maintaining high-quality patient care. This comprehensive review examines the integrated contributions of medical, nursing, diagnostic, and allied health services in building and sustaining resilient healthcare systems. Drawing on recent peer-reviewed literature, the review synthesizes evidence on how multidisciplinary collaboration, flexible clinical decision-making, workforce adaptability, diagnostic continuity, and supportive allied health services collectively enhance system responsiveness and stability. The findings demonstrate that resilience is not the result of isolated departmental efforts, but rather an emergent property of coordinated, system-wide interactions supported by effective governance and digital infrastructure. Nursing services play a pivotal frontline role, while diagnostic and allied health services ensure continuity, safety, and recovery across the care continuum. This review offers an integrated perspective that advances current understanding of healthcare resilience and provides practical insights for policymakers, healthcare leaders, and researchers seeking to strengthen system preparedness and performance in the face of future crises.